Engaging diverse populations in aging research during the COVID-19 pandemic: Lessons learned from four National Institutes of Health funded-Centers - Vega, Irving E.; Ajrouch, Kristine J.; Rorai, Vanessa; Gadwa, Renee; Roberts, J. Scott; Nyquist, Linda (Frontiers in Public Health, 2023)
Background: The COVID-19 pandemic’s impact on our personal and professional lives required a rapid adaptation to the evolving health crisis and accumulating social stresses. Established measures to reduce the spread of infection and potential death had a direct effect on ongoing research that involved older adults and underrepresented racial/ethnic groups. Although important to preserve public health, these measures risk further isolation of vulnerable research participant populations and threatened established community partnerships. To address the social and research challenges evolving from the COVID-19 pandemic, four National Institutes of Health funded-Centers that engage with community members to enhance research and advance the science of aging came together to learn from each other’s efforts, approaches, and communication with community partners. Methods: Monthly meetings served as a venue to discuss the challenges of engagement with research participants and support community partners during of the pandemic. The developed learning community also contributed to recognize and address research staff stress and isolation. We describe how these conversations led our Centers to address unprecedented challenges and sustain community engagement within diverse populations, especially Black/African Americans, Latinos, Middle Eastern/Arab Americans and the oldest-old. Results: The exchange of information resulted in maintain long standing community relationships and partnerships in the face of the uncertainties generated by the pandemic. The strategies included adapting education programs to reduce risk of infection, recognizing symptoms, promoting vaccination and understanding of the effect of COVID-19 to the brain. Different strategies were used to address the effects of isolation and maintain community engagement. Although new research participant enrollment was a challenge, telephone and virtual visits allowed research participants to remain active in research. Community members participation in virtual learning events was variable, ranging from a dozen to hundreds of participants. Invitations to organize panels about newly developed topics indicated the need for information from trusted sources. Conclusions: In sum, the COVID-19 pandemic re=directed all four Centers’ commitment to community service led to develop strategies for social support, which will potentially contribute to transforming public perceptions about research and researchers.